2019
DOI: 10.1111/jcmm.14492
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus lactone attenuates osteoclastogenesis and osteoclast‐induced bone loss by modulating NF‐κB signalling pathway

Abstract: Osteolysis is characterized by overactivated osteoclast formation and potent bone resorption. It is enhanced in many osteoclast‐related diseases including osteoporosis and periprosthetic osteolysis. The shortage of effective treatments for these pathological processes emphasizes the importance of screening and identifying potential regimens that could attenuate the formation and function of osteoclasts. Dehydrocostus lactone (DHE) is a natural sesquiterpene lactone containing anti‐inflammatory properties. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
(53 reference statements)
3
23
0
Order By: Relevance
“…Finally, the downstream reaction, including catabolic enzymes and inflammatory cytokines, is upregulated. A previous study reported that DHE significantly inhibited RANKL-induced osteoclast formation via the NF-κB pathway (Hu et al, 2019). Our study demonstrated similar results-that DHE significantly inhibited the phosphorylation of IKKα, IκBα, and p65 and blocked the degradation of IκBα in TNF-α-induced NP cells.…”
Section: Dhe Ameliorated the Progression Of Idd In A Mouse Model Of Spinal Instability In Vivosupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, the downstream reaction, including catabolic enzymes and inflammatory cytokines, is upregulated. A previous study reported that DHE significantly inhibited RANKL-induced osteoclast formation via the NF-κB pathway (Hu et al, 2019). Our study demonstrated similar results-that DHE significantly inhibited the phosphorylation of IKKα, IκBα, and p65 and blocked the degradation of IκBα in TNF-α-induced NP cells.…”
Section: Dhe Ameliorated the Progression Of Idd In A Mouse Model Of Spinal Instability In Vivosupporting
confidence: 89%
“…All surgical procedures were performed under general anesthesia using 3% isoflurane, were approved by the Institutional Animal Care and Ethics Committee of Ninth People's Hospital, Shanghai Jiaotong University School of Medicine (Shanghai, China), and were performed in accordance with the principles and procedures of the National Institutes of Health Guide for the Care and Use of Laboratory Animals and the Guidelines for Animal Treatment of Shanghai Jiaotong University. After the model was established, the mice were given DHE (20 mg/kg, 120 µl), according to previous research (Wang J. et al, 2017;Hu et al, 2019), or PBS (120 µl) once a day through intraperitoneal injection. Eight weeks after surgery, mice were sacrificed by surgical dislocation, and the lumbar spinal tissues were harvested and fixed in 4% PFA for subsequent downstream analyses.…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Different biomaterials in particulate form exert different types and degree of adverse effects on osteolysis (Longhofer, Chong, Strong, Wooley, & Yang, 2017). Some studies reported that all particulate biomaterials caused significant increases in membrane thickness compared with control (saline) air pouches, with the highest reaction seen in response to titanium particles (Hu et al, 2019). Longhofer et al (2017) found that there were significantly more cathepsin K‐positive osteoclast‐like cells in specimens from titanium particles.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydrocostus lactone also inhibited potassium outflow, which may be responsible for the potent inhibition of NLRP3 and the weak inhibition of AIM2 ( Chen, Li, et al., 2020 ). Dehydrocostus lactone is reportedly involved in regulating NF-κB pathways in acute lung injury and bone metabolic disease ( Hu et al., 2019 ; Nie et al., 2019 ). Chen et al.…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%